Determination of leadership style, discipline and work environment on employee performance through employee job satisfaction at the Bintan District Health Center - Filya Fatriasari; Chabullah Wibisono; I Wayan Catrayasa (LPPM STIE KRAKATAU, 2024)
Purpose: This study aimed to determine and analyze the determinants of leadership style, discipline, and work environment on employee performance through employee job satisfaction at the Bintan Regency Community Health Center. Research Methodology: This type of research uses associative causality design. Data were collected using a questionnaire that was distributed to 236 respondents. Statistical data analysis uses structural equation modeling partial least squares (SEM-PLS) and analysis paths to test relationship patterns that reveal the influence of variables on other variables, both direct and indirect. Results: The research results show that Leadership Style directly has a positive and significant effect on Performance with P-Values of 0.041 < 0.05. Direct discipline had a positive and significant effect on performance, with P-values of 0.002 < 0.05. The work Environment has a positive and significant effect on Performance with P-Values of 0.004 < 0.05. Job Satisfaction has a positive and significant direct effect on Performance with P-Values of 0.006 < 0.05. Leadership Style has a positive but not significant effect on Job Satisfaction with P-Values of 0.065 > 0.05. Discipline directly had a positive and significant effect on Job Satisfaction with P-Values of 0.003 < 0.05. The work Environment directly has a positive and significant effect on Job Satisfaction with P-Values of 0.010 < 0.05. Job Satisfaction did not mediate the influence of Leadership Style on performance, with a p-value of 0.553 > 0.05. The mediating effect of Discipline Job Satisfaction on performance had a p-value of 0.003 < 0.05. The mediating effect of Work Environment Job Satisfaction on performance had a p-value of 0.023 < 0.05.